Faktor Risiko yang Mempengaruhi Terjadinya Komplikasi Kardiovaskular Pasca Pembiusan/Sedasi Prosedural pada Pasien Pediatri - Djajantisari; hendra, hendra hermawan; Widyastuti, Yunita (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2023)
Background: The morphology and physiology of neonates and children differ from those of adults. The most common complications encountered involve respiratory issues followed by cardiovascular problems. The predominant cardiovascular complications in the field of pediatric anesthesia are hemodynamic instability followed by cardiac arrest. Perioperative cardiovascular complications are closely related to a history of prematurity under the age of 1 year, ASA physical status ≥3, concomitant cardiovascular or metabolic diseases, emergency surgeries, and surgical procedures. To date, few risk factors related to the cardiovascular system have been identified in pediatric anesthesia. Objective: To identify risk factors influencing the occurrence of post-anesthesia/sedation cardiovascular complications in pediatric patients at Dr. Sardjito Hospital, Yogyakarta. Method: The research design employed in this study was a prospective cohort observation of pediatric patients undergoing anesthesia or procedural sedation at Dr. Sardjito Hospital. Research subject data included demographic characteristics, ASA status, history of concomitant diseases, type of surgery, urgency level, and post-anesthesia complication occurrences. Data normality was tested using the Kolmogorov-Smirnov test, bivariate analysis was conducted using the Fisher test, variables with p-value <0.25 underwent multivariate analysis using logistic regression for categorical data. The results were processed using SPSS version 23.00. Results: A total of 181 subjects were predominantly male patients aged >5 years. Factors influencing post-anesthetic cardiovascular complications included ASA physical status ≥3 (p=0.033) OR 8.96 (95% CI 2.07 – 38.89), emergency procedures (p=0.043) OR 12.63 (95% CI 1.08 – 147.15), age >5 years (p=0.033) OR 5.67 (95% CI 1.15 – 28.1), female gender (p=0.001) OR 7.85 (95% CI 2.23 – 27.71), and type of surgical procedure (p=0.017) OR 16.64 (95% CI 1.63 – 169.05). Conclusion: Age >5 years, female gender, ASA physical status ≥3, emergency procedures, and surgical procedures are risk factors associated with the occurrence of post-anesthetic/sedation cardiovascular complications in pediatric patients.